Peer Review - SELECTION OF MULTIPLE EARTHQUAKES CONSIDERING VERTICAL GROUND MOTION TO STRUCTURES - Ade Faisal (KUMPULAN JURNAL DOSEN UNIVERSITAS MUHAMMADIYAH SUMATERA UTARA, 2017)
Current earthquake engineering field ignores the vertical ground motion in design and analysis of the structure system even though in actual condition these two phenomena impose the significant effect to the structure system. The repeated earthquake happened everywhere all over the world with the short time interval while earthquake in vertical excitation also reported as quantitatively occur but always ignored. Therefore, this study attempts to assess the behaviour of structures due to multiple earthquakes with vertical component. For that purpose, this study processed and tabulated more than 500 ground motion data that was recorded all over the world. The data was downloaded from Pacific Earthquake Engineering Research center – New Generation Attenuation (PEER-NGA) database, As a result, About 24% (121 records) of the listed earthquake records show V/H value more than 0.67 or 2/3 rules and most of the event occurred with source distance less than 50km. About 8.0% (40 records) of the showed V/H ratio more than 1.0 with the highest ratio is 4.85 named Borrego in 1942. It seems that vertical ground motion were also one of the factor effecting analysis and design of structures.